The Influence of Alcohol Marketing Channels on Alcohol Consumption: A Quantitative Study of Students Residing in the Western Cape, South Africa - Mackay, Brett (The IIE, 2016)
The generally held viewpoints about alcohol and advertisements have evolved in recent years (Gunter, Hansen & Touri, 2009; Gordon et al, 2010; Jones & Magee, 2011). The objective of this study was to determine if the influence of alcohol advertising channels is significantly related to the frequency of alcohol consumption by students. A quantitative survey was conducted targeting students residing in the Western Cape, South Africa. This empirical analysis highlighted that marketing channels are able to influence the consumption levels of alcohol by students, especially more contemporary marketing channels like the internet or television. These contemporary channels are discussed in further detail as they are a significant subject throughout the study. The study also measured whether advertising channels were the best strategy to influence consumption behaviour of individuals, however, this was found not to be the case. The findings suggested that although advertising does influence their purchasing decisions, other factors are more influential.
Keywords: Alcohol advertising; Alcohol consumption; Marketing